Certain Classes of Analytic Functions Bound with Kober Operators in q-Calculus. (21st June 2021) - Purohit, S. D.; Gour, M. M.; Joshi, S.; Suthar, D. L.
Abstract : Through applying the Kober fractional q -calculus apprehension, we preliminary implant and introduce new types of univalent analytical functions with a q -differintegral operator in the open disk U = ξ ∈ ℂ : ∣ ξ | < 1 . The coefficient inequality and distortion theorems are among the results examined with these forms of functions. Specific cases are responded and addressed immediately. The findings include an expansion of the numerous established results in the q -theory of analytical functions.